Vibrational Spectrum and Normal Coordinate Analysis of p-Toluidino-pchlorophenylglyoxime - Arslan, Hakan; Ozpozan, Talat (Asian Journal of Chemistry, 2010)
A complete vibrational assignment of the solid-state IR spectrom of p-toluidino-p-chlorophenylglyoxime was performed on the basis of normal coordinate analysis of a single molecule, assuming Cs point group symmetry. The calculated normal frequencies were in good agreement with the experimental one.